A certain family of bi-univalent functions associated with the Pascal distribution series based upon the Horadam polynomials - H. M. Srivastava; A. K. Wanas; G. Murugusundaramoorthy (Surveys in Mathematics and its Applications, 2021)
The purpose of this article is to introduce a new subclass ℋΣ(δ,λ,m,θ,x) of analytic and bi-univalent functions by using the Horadam polynomials, which is associated with the Pascal distribution series and to investigate the bounds for |a2| and |a3|, where a2, a3 are the initial Taylor-Maclaurin coefficients. Further we obtain the Fekete-Szegö inequality for functions in the class ℋΣ(δ,λ,m,θ,x) which we have introduced here.